Public television and cultural diversity: the case of programs addressed to «immigrants» - Navarro, Laura (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
This article analyses the emergence of TV programs addressed to «immigrants» in Spain, from an historical and sociological perspective, which shows the influence of social, political and economic context of the country on the creation of these programs, and points out the pioneer role of local and autonomic public televisions on their promotion. In addition, the analysis of the evolution and disappearance of Con todos los acentos (TVE) and Andalucía sin fronteras (Canal Sur TV) shows the commercialisation of contents and the precarization of technical and human resources experienced —specially since 2008— by these TV programs, which were created at the beginning to promote immigrant population’s «integration» and the awareness of «diversity».
Keywords: immigration; public television; migrant journalists; cultural diversity; racism